Avaliação de pacientes: estudo da concordância entre duas abordagens - instrumento de classificação e raciocínio clínico - Paschoal, Josi Vaz de Lima (2012)
Introduction: The increasing complexity of nursing work demands fast and accurate decision-making skills about patients care needs. Assessment is one of the tools professional use to identify these needs and guides care actions. Aims: This descriptive and exploratory study aimed to: 1. analyze agreement and disagreement between assessments made through clinical reasoning and application of a patient classification instrument and, 2. investigate the association between the agreement and the professionals personal (age) and professional characteristics (function, professional experience and time on the job, professional and academic qualification, working at an Intensive Care Unit or another hospitalization unit). Method: 105 adult patients were investigated, hospitalized at a teaching hospital in the interior of São Paulo State between May and January 2011). Each patient was assessed by three nurses active at six hospitalization units or not and using a classification instrument or not. To verify the inter-rater agreement level, weighted kappa statistics were used 95% CI and, to investigate the association between agreement and personal characteristics, the Bootstrap method. Results: Inter-rater agreement indicated: kw 0.87 very good level (instrument x internal evaluator), Kw 0.78 (instrument x external evaluator) and Kw 0.76 (among evaluators), considered a good level. The main care areas the nurses identified were Research and Monitoring, Locomotion and Activity and Bodily Care and Eliminations. The mean number of care areas identified in the assessments by the internal evaluator was 2.8 (1.8), against 3.5 (1.6) by the external evaluator. The personal and professional characteristics that influenced inter-rater agreement were: age ≥ 30 years 0.73(0.08), professional experience ≥ 5 years 0.73 (0.08), professional qualification 0.83 (0.08) and working at an Intensive Care Unit 0.80 (0.11) for the internal evaluator. As for the external evaluator, the following results were observed: academic qualification 0.19 (0.26) and time on the job ≥ 2 years 0.14 (0.13). Conclusion: The assessments based on clinical reasoning and the classification instrument similarly identified patients nurse care demand and care categories (care profile), although many areas were not addressed in the nurses clinical assessment.